WAYS TO RESTORE THE FRUIT GARDEN AND IMPROVE EFFICIENCY - Usmonov Saminjon Olimovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article deals with horticulture, gardening, selection of early and high yielding varieties, selection of places for gardening.